The Variety Of Tauhid Education Methods at Al-Amien Islamic Boarding School Purwokerto Wetan Banyumas - Mochammad Sidqi Awwaliya Rahman; M. Slamet Yahya (International Journal of Education, Vocational and Social Science, 2022)
This research aims to identify the numerous interpretations of tauhid education that are presented through diverse learning techniques, as well as their underlying significance. This field research (Field Research) employed a descriptive-qualitative approach. Various instruments, including interviews, observations, and documentation, were employed by researchers to collect data. Data reduction, data visualization, and conclusion-drawing are the methods used in this research's analysis. This research revealed that (1) there were several ways that the Koran was received at Al-Amien Islamic Boarding School, including (a) exegesis reception (lecture method), which involved reciting the monotheistic holy book, and (b) aesthetic reception (inquiry method), which involved displaying verses of the Koran written in calligraphy; (c) Reciting shalawat jibril and nadham aqidatul awwam facilitates functional reception (AIR technique). (2) Among the connotations attached to each style of reception are the following: (a) objective significance as a form of obedience, preservation of traditions, and growth of faith; (b) As a manner of scientifically strengthening monotheism, enhancing awareness of variety, and fostering tranquillity, expressive meaning is a means of enhancing monotheism's expressive significance; (c) documentary significance, as a type of localization of the entire civilization